Influence of trace mineral concentration and source on yearling feedlot steer performance, carcass characteristics, and trace mineral status - Berrett, Cari J., author; Engle, Terry E., advisor; Wagner, John J., committee member; Brummer, Joe E., committee member (Colorado State University. Libraries, 2013)
Effects of trace mineral (TM) concentration and source on yearling feedlot steer performance, carcass characteristics, and liver TM status, were determined utilizing 360 crossbred steers (initial BW=350 ± 4.0 kg). Steers were blocked by initial BW and randomly assigned to one of 4 treatments (10pens/treatment; 9 hd/pen). Treatments consisted of: 1) negative control (NC), no supplemental TM (basal diet contained 7.65 mg Cu/kg DM, 50.5 mg Zn/kg DM, 27.7 mg Mn/kg DM, and 0.12 mg Co/kg DM); 2) basal diet supplemented with 10 mg Cu/kg DM from CuSO4, 30 mg Zn/kg DM from ZnSO4, 20 mg Mn/kg DM from MnSO4, 0.50 mg I/kg DM from EDDI, 0.10 mg Se/kg DM from Na2O3Se, and 0.10 mg Co/kg DM from CoCO3 (NRC); 3) basal diet supplemented with inorganic forms of Cu, Zn, Mn, EDDI, Se and Co at consulting nutritionist recommendations (CNI, 20, 100, 50, 0.50, 0.20, and 0.20 mg of mineral/kg DM, respectively); and 4) basal diet supplemented with 66.6% inorganic and 33.4% organic Cu, Zn, Mn and Co, and inorganic forms of I and Se at iso-concentration to consulting nutritionist recommendations of treatment 3 (CNO). All steers were fed a high concentrate, steam-flaked, corn-based diet for 154 d. Steers were individually weighed on d -1, 0, 35, 121, 153, and 154. Continuous data were analyzed on a pen mean basis using a mixed model appropriate for a randomized block design (fixed effects = treatment and time; random effect = replicate). Categorical data were analyzed utilizing GLIMMIX (fixed effect = treatment; random effect = replicate). Initial and final BW, ADG, DMI, F:G and G:F ratios and calculated net energy recoveries were similar (P > 0.23) across treatments. Subcutaneous adipose tissue depth, HCW, KPH, yield grade, marbling score, and quality grade were similar across treatments (P > 0.17). Final liver Zn, Mn, Se, and Co concentrations were similar across treatments (P > 0.37). Under the conditions of this experiment, it appears that basal dietary concentrations of Cu, Zn, Mn, and Co were adequate for growth and performance of finishing yearling feedlot steers. For experiment 2, an in vitro analysis was utilized to determine "releasability" of trace minerals from the basal diets fed in experiment 1. Three tubes for each treatment ration as listed for experiment 1 were incubated for 0, 6, 12, and 24 h in a 3:1 ratio of modified McDougall (1984) buffer and rumen fluid taken from steers fed high a concentrate finishing diet. Dry matter disappearance percentage was similar across treatments (P > 0.49). Percent Cu released was significantly different (P > 0.02) for treatment where NC was less than Suppl, and percent Zn released was also significant (P > 0.0004) for treatment NC was also lower than Suppl. From the simulated conditions of the second experiment, it appears there are differences in the ration "releaseabilities" of Cu and Zn from the simulated abomasal and ruminal conditions from treatment diets.
Keywords: beef cattle; trace minerals; feedlot